Outside the rules, outside the boundaries - Erkkilä-Hill, Jaana (Amsterdam University Press, 2024)
The following contribution is a written account of Jaana Erkkila-Hill’s keynote lecture at the FORUM+ symposium The art school as an ecosystem: Future perspectives on higher arts education, co-organised with ARIA during the research festival ARTICULATE on 20 October 2023.
Keywords: taidekasvatus; opetus; taidepedagogiikka; taidekorkeakoulut; taiteellinen työ; taiteilijat; pedagogiikka